Regulatory encounters : multinational corporations and American adversarial legalism - Axelrad, Lee, 1963-; Kagan, Robert A. (Berkeley : University of California Press, 2000)
This work reports on a path-breaking study of how government regulation of business in the United States differs in practice from regulation in other economically advanced democracies. In each of ten in-depth case studies, the contributors to this volume compare a particular multinational corporation's experience with parallel regulatory regimes in the United States and in Japan, Canada, Great Britain, Germany, the Netherlands, and the European Union, noting precisely which regulatory precautions were actually implemented in each country.
Union / Lori A. Johnson, Tatsuya Fujie, and Marius Aalders -- The consequences of adversarial legalism / Robert A. Kagan.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: International business enterprises -- Law and legislation -- United States; International business enterprises -- Law and legislation; Adversary system (Law); Entreprises multinationales -- Droit -- États-Unis.; Entreprises multinationales -- Droit; Système accusatoire (Droit); LAW -- Administrative Law & Regulatory Practice; Adversary system (Law); International business enterprises -- Law and legislation; United States; Internationale ondernemingen; Rechtsstelsels; Bewijslast; Entreprises multinationales -- Droit -- Etats-Unis -- Etudes comparatives; Système accusatoire et système inquisitoire -- Etats-Unis -- Etudes comparatives; Jura -- Jura